Formulasi Emulgel Ekstrak Bawang Putih (Allium sativum L.) - Widyasari Putranti; Akmal Maulana; Siti Fatmawati Fatimah (Fakultas Farmasi Universitas Andalas, 2019)
Garlic have an activity as antifungal. Garlic extract need to be non spesific standarized to get consistent quality. Emulgel have hydrophobic or hidrophilic active substances because emulgel is a combination of emulsion and gel. This study aims to obtain the garlic extract emulgel formula which has good quality and good physical properties.The garlic extraction method maceration method with ethanol 96% as a solvent (1:7.5). Non spesific parameter of extract standardization were powder lost on drying, water content, ash content, acid-insoluble ash content, mass of extract spesification. Extract were standardized and then formulated in emulgel dosage form with 25% concentration of extract, then emulgel evaluated for physical properties include organoleptic test, homogeneity, pH, temperature stability, spreadability, stickiness, type of emulsion, and viscosity. The results showed rendemen of extract (8.90 ± 0.12)%, lost on drying (6.85 ± 0.11)%, water content of extract (4.16 ± 1.4)%, ash content of powder (3.24 ± 0.02)% and extract (1.14 ± 0.03)%, acid-insoluble ash content powder (0.96 ± 0.02)% and extract (0.61 ± 0.07)%, the mass of extract spesification 1.028, and for the physical properties test of emulgel preparations obtained homogeneous emulgel, semisolid form, light brown color, smell of extract garlic, stable at 5ºC and 25ºC for 24 hours, pH 7, spreadability (2.49±0.12) g.cm.s-1, stickiness (61.99±5.81)seconds, type of emulsion o/w, viscosity(2.63±0.22) Pa.s. Based on the study was obtained garlic extract that fulfill the requirements of non spesific parameter standardization from Farmakope Herbal Indonesia and emulgel formulation of garlic extract has good physical properties.